The Effect of Cooperative Learning and Self Confidence on Service Volleyball At SMPN 4 Negara - Rizkei Kurniawan; Desy Tya Maya Ningrum; Yafi Velyan Mahyudi (JIPES - JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2019)
Abstract : The aim of this study was determine difference cooperative learning TGT (Teams Game Tournament) and STAD (Students Teams-Achievement Divisions) and students confidence in the service volleyball. The subjects were conducted in students of grade VIII SMPN 4 Negara. This research uses treatment by level 2 x 2. Number of samples is 48 students. Data analysis technique is the analysis of two-way variance (ANAVA) and then followed by Tukey test at significance level α = 0,05. Results of this study showed that 1) results value of service volleyball use method TGT (Teams Game Tournament) is higher than STAD (Students Teams-Achievement Divisions) at SMPN 4 Negara, 2) There is an interaction between cooperative learning (A) and student confidence (B) on the results of service volleyball at SMPN 4 Negara. The value of results service volleyball on cooperative learning TGT (Team Game Tournament) student high confidence (A1B1) is higher than STAD (Student Teams-Achievement) students high confidence (A2B1) at SMP Negeri 4 Negara. The value of results service volleyball on cooperative learning TGT (Team Game Tournament) student low confidence (A1B2) is lower than STAD (Student Teams-Achievement) students low confidence (A2B2) at SMP Negeri 4 Negara.